2010
DOI: 10.1016/j.aller.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Specific pattern of flea antigen recognition by IgG subclass and IgE during the progression of papular urticaria caused by flea bite

Abstract: The predominant specific antibody isotypes vary according to the time elapsed since the onset of symptoms in papular urticaria caused by flea bite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
1
10
0
5
Order By: Relevance
“…En estudios en perros se han identificado tres alérgenos de pulga (39). También, hay estudios en humanos en los cuales se ha demostrado que los pacientes con urticaria papular generan IgE con varios componentes del extracto de pulga (26,40).…”
Section: Agentes Etiológicosunclassified
See 3 more Smart Citations
“…En estudios en perros se han identificado tres alérgenos de pulga (39). También, hay estudios en humanos en los cuales se ha demostrado que los pacientes con urticaria papular generan IgE con varios componentes del extracto de pulga (26,40).…”
Section: Agentes Etiológicosunclassified
“…En un estudio, la reacción de la IgE a bandas en el rango de 31 a 35 kDa fue alrededor de dos veces más frecuente en los casos de urticaria papular que en los controles. Por otra parte, las bandas de 16 a 20 kDa fueron reconocidas por 33,4 % de los pacientes, pero por ninguno de los sujetos de control (40). Cuando se hicieron pruebas de activación de basófilos con fracciones de distinto peso molecular del extracto de cuerpos de pulga, se encontró que, en las bandas de menos de 50 kDa y en las de 50 a 100 kDa, el promedio de expresión del marcador de activación CD63 era mayor en los niños con urticaria papular (57).…”
Section: Respuesta Humoralunclassified
See 2 more Smart Citations
“…Studies of the immune response have shown a differential IgE and IgG antibody response among patients, depending on the time of evolution of the disease [1,2] and the pattern of cellular infiltration at the lesion site consisting primarily of eosinophils and CD4 + T lymphocytes [2]. Furthermore, a predominantly Th2 response to a polyclonal stimulus [3] and functional differences in monocyte-derived dendritic cells (DC) from patients compared to those originating from healthy donors has also been described [4].…”
Section: Introductionmentioning
confidence: 99%